2002
DOI: 10.1002/ajim.10037
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical models for the pathogenesis of specific distal upper extremity disorders

Abstract: It is possible to propose biologically plausible models of pathogenesis that are both coherent with current knowledge of tissue responses and consistent with clinical observations; however, more than one model was plausible for some conditions. Additional research is needed to determine which, if any, of the proposed models might be correct. Such models may be useful to health care providers and ergonomists in the context of primary, secondary, or tertiary prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…Aside from the carpal tunnel contents, the morphological and mechanical changes (e.g. hypertrophying and stiffening) of the TCL may be a causative factor in CTS [11, 26, 30, 37, 42]. Such pathological changes of the TCL may reduce the amount of space available to the carpal tunnel contents or compromise the inherent compliance of the carpal tunnel structure, both of which may negatively implicate the median nerve.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from the carpal tunnel contents, the morphological and mechanical changes (e.g. hypertrophying and stiffening) of the TCL may be a causative factor in CTS [11, 26, 30, 37, 42]. Such pathological changes of the TCL may reduce the amount of space available to the carpal tunnel contents or compromise the inherent compliance of the carpal tunnel structure, both of which may negatively implicate the median nerve.…”
Section: Introductionmentioning
confidence: 99%
“…The transverse carpal ligament (TCL) plays an important role in regulating carpal tunnel mechanics [1]. In particular, hypertrophy of the TCL has been postulated as one of the underlying pathogenic mechanisms of carpal tunnel syndrome [2]. Imaging studies have shown that the TCLs were thickened in individuals with carpal tunnel syndrome [3].…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies have shown pathological changes of the TCL including its stiffening and hypertrophying [16–18, 20]. Hypertrophy of the TCL and/or tendons limits the available space within the carpal tunnel for the median nerve and promotes carpal tunnel stenosis, an etiological factor of carpal tunnel syndrome [2830]. The findings from this study show that increased finger loading and the deviated posture of wrist flexion amplify the TCL-tendon interaction, thereby potentially increasing the risk of maladaptation.…”
Section: Discussionmentioning
confidence: 99%